Introgression From Genetically Modified Plants Into Wild Relatives 2004
DOI: 10.1079/9780851998169.0235
|View full text |Cite
|
Sign up to set email alerts
|

A review on interspecific gene flow from oilseed rape to wild relatives.

Abstract: One of the main concerns about the commercial release of transgenic crops is the likelihood of transgene spread from cultivated species into wild relatives. This question is relevant for oilseed rape/canola (Brassica napus, AACC, 2n=38), as this species is partially allogamous with several wild relatives that are often sympatric with oilseed rape production. A workshop sponsored by the European Science Foundation (11-13 June 2001, Rennes, France) was held: (i) to identify the main weeds present in European and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 0 publications
2
62
0
Order By: Relevance
“…Some of these vegetables are left unharvested and flower in the following spring. Interspecific hybridization between Brassica crops can occur under natural conditions, although the results of hybridization potential differ among various reports (e.g., Chèvre et al, 2004;FitzJohn et al, 2007;Ford et al, 2006;Jørgensen et al, 1996;Légère, 2005;Sheffler and Dale, 1994;Stewart et al, 2003;Warwick et al, 2003;Wilkinson et al, 2003). Allainguillaume et al (2006) reported that the fitness decline of hybrids between B. napus and B. rapa in the United Kingdom acted as a means of natural biological containment.…”
Section: Provenance and Environmental Concern Of Oilseed Rape Plants mentioning
confidence: 67%
“…Some of these vegetables are left unharvested and flower in the following spring. Interspecific hybridization between Brassica crops can occur under natural conditions, although the results of hybridization potential differ among various reports (e.g., Chèvre et al, 2004;FitzJohn et al, 2007;Ford et al, 2006;Jørgensen et al, 1996;Légère, 2005;Sheffler and Dale, 1994;Stewart et al, 2003;Warwick et al, 2003;Wilkinson et al, 2003). Allainguillaume et al (2006) reported that the fitness decline of hybrids between B. napus and B. rapa in the United Kingdom acted as a means of natural biological containment.…”
Section: Provenance and Environmental Concern Of Oilseed Rape Plants mentioning
confidence: 67%
“…Cheng et al (2002) Bn)Raphanus raphanistrum L. (n09) Eber et al (1994), Baranger et al (1995), Chadoeuf et al (1998), Che`vre et al (1998a, Darmency et al (1998), Lefol et al (1997), Rieger et al (2001), Gue´ritaine et al (2003a, b), Che`vre et al (2003Che`vre et al ( , 2007 [Bn)Raphanus raphanistrum F 1 ] R. raphanistrum Che`vre et al (1997Che`vre et al ( , 1998a Bn)Raphanus sativus L. (n09) Gupta ( (1991, 1996b), Alam et al (1992), Sharma and Singh (1992), Vijayakumar et al (1994), Frello et al (1995), Rao and Shivanna (1997), Gupta (1997), Sandhu and Gupta (2000), Choudhary and Joshi (2001a) et al (1985), Ringdahl et al (1987), Salisbury (1989), Gupta (1997) Diplotaxis siifolia Kunze (n010))Bn Gupta (1997) Hirschfeldia incana)Bn Lefol et al (1996b), Darmency and Fleury (2000) Raphanus raphanistrum)Bn Eber et al (1994), Baranger et al (1995), Darmency et al (1998), Che`vre et al (1997, 1998a, 2000, Gue´ritaine and Darmency (2001), Rieger et al (2001), Gue´ritaine et al (2002Gue´ritaine et al ( , 2003a Leckie et al (1993): Jorgensen and Andersen (1994), Bin...…”
Section: Female Parent)male Parent Citationmentioning
confidence: 99%
“…Volunteers are plants emerging within agricultural fields as a result of previous cropping, while feral plants are domesticated plants reverting to the wild type outside the cropped area. Important steps in vertical gene flow are the spread of the (trans)gene(s) to other plants or populations, the formation of F 1 hybrids, and the stabilisation of the (trans)gene(s) by introgression (Chèvre et al, 2004;Ellstrand, 2003;Jenczewski et al, 2003;van Tienderen, 2004). In oilseed rape, the (trans)gene(s) can be spread in space through pollen and seeds, and in time through seeds in the seed bank (Eastham and Sweet, 2002;Rieger et al, 1999;Salisbury, 2002;Warwick et al, 2004).…”
Section: Vertical Gene Flow In Oilseed Rapementioning
confidence: 99%